Islamic Commodification in Representation of Political Development in Indonesia: A Systematic Literature Review - Dodi Suryana; Tito Handoko (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2023)
The phenomenon of the commodification of religion in politics does not only occur in Indonesia, but western countries have also already experienced that phase. This can be understood because of the development of western democratic life, which emphasizes individual freedom and limits the role of the state in religious activities. Likewise, with religious life in developing countries (read Indonesia), there is a notion saying that religion has even become a milestone for the establishment of the state. The unity of religious leaders, for example, is a force that can mobilize a spirit of unity and integrity. In the practice of democracy in Indonesia, the support of Indonesian Muslims for democratic values can then be considered concerning the behavior of Islamism (Muslim worship). Thus, this study critically and qualitatively examines how the commodification of Islam in the representation of political development in Indonesia from various related articles. Based on these concerns, a systematic literature review was used as a method of analyzing national and international journal articles from nine managed databases. From the literature review, there were thirty (30) relevant research-based articles in the last 10 years from 2010 to 2020 selected from Google Scholar, Taylor, Francis Outline, Springer Link, Emerald Insight, Science Direct, Sage Journal Online, and Oxford Cambridge. Three stages are carried out: preparation, data screening and validation, and content review. The findings cover: 1) the value of Islam in the representation of political development in Indonesia, 2) the form of commodification of Islam in the representation of political development in Indonesia, 3) the implications of the commodification of Islam in political development in Indonesia.